Comportamento de preços na revenda do etanol e da gasolina na cidade de Sorocaba - Pistelli, Ana Carolina Martins Alves (2019)
The purpose of this study was to investigate the characteristics and regulation of the fuel retail market in order to analyze the behavior of the prices practiced by retailers of liquid fuel (Hydrous Ethanol and Gasoline C) and, thus, understand the strategic behavior of these agents in order to identify signs of spatial dependence and of rivalry and/or cooperation. On the competitive aspect, it is possible to conclude that the market of liquid fuel is composed of many fuel retailers, although the competitive strategy lies with few agents, in other words, the major distributors define the main strategies related to brand recognition, additional services and pricing. Jointly with the significant barriers to institutional entry, the sprayed demand and the active presence of the unions and associations, such aspects could facilitate the exercise of market power, thereby reducing social/economic welfare. The empirical analysis uses data of hydrous ethanol and gasoline C in the city of Sorocaba, between January 2014 and June 2017. The analysis of the behavioral pattern of fuel retail in a spatial context, that is, the interaction between the change in fuel prices at a given gas station and its influence on and/by the events at neighboring gas stations and the findings for both fuels, hydrous ethanol and gasoline C, shows the existence of a spatial relationship among prices practiced by retail establishment in the city. In other words, a change in the price of ethanol or gasoline by a gas station dealer influences the prices of those fuel at neighboring stations, and the results also indicate that the closer the gas stations are located, the greater the impact on price changing by a neighboring gas station. In sequence, the temporal analysis of prices allowed to verify the existence of long-term relation between resale prices and to identify the direction and value of those reactions. Although it is not possible to establish a behavioral pattern for all the gas stations, in general, regarding the bilateral price reaction by ethanol and gasoline retail sales, the end result of this study indicates greater signs of cooperation rather than of competition among resellers on their price setting. It is worth mentioning, however, that in this study, the signs of cooperation verified through the analysis of the elasticity of the response from neighboring resellers on the price settings do not mean cartelized behavior among the resellers that were analyzed.